(3GdWH GdYOdj GdbVGFj (B/s - (3GdCSOj, VjGA YHO Gddg YHhO LGHQs; (3YHO GdMejOGhj, CMeOs ((3YeGf, GdCQOf (B:s (3GdOGQ GdefgLjI ddfTQ hGdJhRjY,s, 2018)
(3Ef cTa GdMbjbjI gh JeGe eG jSYi Edjg GdbGVj YfOeG JYQV Ydjg OYhi eG, hef hGLHg Cf jJMQi YfgG, hjJNP GdELQGAGJ GdcajdI HPdc, hjHMK Yf cGaI GdCOdI GdJj JhUdg EdjgG, hef Hjf gPg GdELQGAGJ GdeSGYOI ddbGVj GdGSJYGfI HGdWH GdYOdj(B. (3Ef ehVhY GdWH GdYOdj GdbVGFj ef GdehGVjY GdegeI hGdNWQI hGdObjbI, agh jHjf GdYdGbI jhVM GdUdI Hjf GdbGfhf GdLfGFj hYde GdWH GdYOdj GdPj jHMK aj GdCSHGH GdeDOjI ddLQjeI ef MjK GdHMK Yf eQJcHgG heMGhdI GdJYQa Ydjg(B.s
(3HHdjhLQGajI (B: (3UaMI (B257-271.s
Keywords: (3GdWHs -- (3bhGfjf hJTQjYGJs; (3GdWH GdTQYjs